Oftalmomiíase externa causada por cochliomyia hominivorax - Takahagi, Rodrigo Ueno [UNESP]; Gonçalves, Fernando Pistarini [UNESP]; Madeira, Newton Goulart [UNESP]; Schellini, Silvana Artioli [UNESP] (My University, 2007)
The purpose of this study was to report a case of external ophthalmomyiasis caused by Cochliomyia hominivorax in a 10 years-old child, which presented acute preseptal celulitis and had 17 worms removed from the lacrimal canaliculus and conjunctival cul de sac, bilaterally, with resolution. The authors discuss the diagnosis and treatment of this nosological entity.
Cochliomyia hominivorax provoking external ophthalmomyiasis
Keywords: Case reports [publication type]; Cellulitis/therapy; Lacrimal apparatus/pathology; Myiasis, eye infections, parasitic; Screw worm infection/therapy